Ventricular Septal Defect Closure with Perforated Patch in Large Ventricular Septal Defect with Severe Pulmonary Hypertension and Non Reactive Oxygen Test - Budi Yuli Setianto; Hariadi Hariawan; Rano Imawan (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2015)
Management of ventricular septal defect (VSD) with severe pulmonary hypertension (PH) had not been extensively studied and is still challenging. The closure of VSD in patients with high pulmonary vascular resistance (PVR) and severe PH is highly risk procedure. If high PVR and severe PH still persist after closure procedure, the patients have poor prognosis. We reported a 24-year-oldwoman whom was diagnosed with large VSD, bidirectional shunt with L to R dominance, dilatation of left ventricle, and mild to moderate mitral regurgitation, mild tricuspid regurgitation and severe PH. Right heart catheterization showed pre-oxygen test: mean aorta pressure 85 mmHg, mean pulmonary artery pressure 65 mmHg, fl ow ratio 5,4, PVR 2,3 WU and pulmonary vascular resistance index (PVRI) 3,22 WU/m2. The results of post-oxygen test: mean aorta pressure 83 mmHg, mean pulmonary artery pressure 63 mmHg, fl ow Ratio 2,2, PVR 0,3 WU and PVRI 0,42 WU/m2. Patient had been performed VSD closure with perforated patch 3 mm. Three month evaluation by echocardiography showed residual VSD 3 mm, L to R shunt, moderate tricuspid regurgitation and mild PH (TVG 36 mmHg). In Baumgartner criteria of VSD operability, this patient was not operable because the ratio of mean pulmonary and systemic circulation more than 2/3, but in Lopez criteria, patient is operable because PVRI below 6 WU/m2. Patient with high and moderate PH and PVR which is still operable, VSD can be closed partially. Partially VSD closure can be performed by transcatheter procedure after PH decrease and stable.Keyword: VSD closure- perforated patch – PH severe